Human papillomavirus infection in healthy women aged 18‒45 years in Panzhihua of Sichuan Province - LI Hua; HUANG Ting; LAN Xi; HUANG Xiaomei (Shanghai yufang yixue, 2024)
ObjectiveTo determine the human papillomavirus (HPV) infection status and possible influencing factors among healthy women aged 18‒45 years, and to provide a scientific evidence for the prevention of HPV infection and cervical cancer.MethodsA total of 23 HPV types were examined by PCR-reverse dot blot hybridization in 1 210 healthy women who voluntarily participated in the study. Infection status of each HPV genotype and possible factors associated with the infection were determined, including age, ethnicity, marital history, pregnancy history, number of sexual partners, and age at first sexual intercourse.ResultsA total of 1 210 healthy women were examined, of which 267 tested positive for HPV, with a prevalence of 22.07%. The prevalence did not differ significantly across age groups or ethnicities (all P>0.05). Moreover, the highest prevalence was found in the divorced/widowed participants (53.57%), compared with other marital status (χ2=35.16, P<0.05). Among the 1 207 participants with pregnancy history, the highest HPV prevalence was 30.58% in those with five or more pregnancies; however, it did not significantly associated with numbers of pregnancies (χ2=10.07, P=0.07). Number of sexual partners showed a significantly positive association with HPV infection (P<0.05). In addition, earlier age at first sexual intercourse was significantly associated with HPV infection (χ2=17.37, P<0.05).ConclusionHealthy women in Panzhihua City were mainly infected with a single HPV type, and the dominant types were HPV 52, 81, and 53. Marital history status, higher number of sexual partners, and younger age at first sexual intercourse were influencing factors associated with HPV infection. It suggested that regular sexual partners and stable marital relationship may reduce the risk of HPV infection.